SURAT KETERANGAN TANAH (SKT) YANG DIBUAT KEPALA DESA SEBAGAI ALAS HAK DALAM RANGKA PENDAFTARAN TANAH - MUH. ZEIN THALIB (Jurnal Yustisiabel, 2019)
This study aims to determine the strength and legal position of land certificates made by the Village Head as the basis of rights in the framework of land registration. The research method used is normative research conducted through library research or library research. In conclusion, the legal strength of the Land Certificate made by the Village Head as the basis of rights in the framework of land registration is an explanation of the land history concerning where the land came from, who physically controlled the land and its boundaries. So that the land certificate serves as evidence of strengthening physical mastery when the applicant does not have or complete proof of his mastery. The legal position of Land Certificate as the basis of rights in the framework of land registration after the issuance of Circular of the Minister of Agrarian and Spatial Planning / Head of the National Land Agency Number 1756 / 15.I / IV / 2016 is no longer needed when the document is incomplete or non-existent. The Circular only requires a statement of mastery of the physical field of land made by the applicant himself and stamped with the name of the witnesses.